Answer:
(- 6, 10 ) and (- 1, 5 )
Step-by-step explanation:
Given the 2 equations
y = x² + 6x + 10 → (1)
y = - x + 4 → (2)
Substitute y = x² + 6x + 10 into (2)
x² + 6x + 10 = - x + 4 ( subtract - x + 4 from both sides )
x² + 7x + 6 = 0 ← in standard form
(x + 1)(x + 6) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 1 = 0 ⇒ x = - 1
x + 6 = 0 ⇒ x = - 6
Equate these values into (2) for corresponding values of y
x = - 1 : y = - (- 1) + 4 = 1 + 4 = 5 ⇒ (- 1, 5 )
x = - 6 : y = - (- 6) + 4 = 6 + 4 = 10 ⇒ (- 6, 10 )